2014
DOI: 10.2217/fmb.13.162
|View full text |Cite
|
Sign up to set email alerts
|

Master Manipulators: An Update on Legionella Pneumophila Icm/Dot Translocated Substrates and their Host targets

Abstract: Macrophages are the front line of immune defense against invading microbes. Microbes, however, have evolved numerous and diverse mechanisms to thwart these host immune defenses and thrive intracellularly. Legionella pneumophila, a Gram-negative pathogen of amoebal and mammalian phagocytes, is one such microbe. In humans, it causes a potentially fatal pneumonia referred to as Legionnaires' disease. Armed with the Icm/Dot type IV secretion system, which is required for virulence, and approximately 300 translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
84
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 90 publications
(135 reference statements)
0
84
0
Order By: Relevance
“…Evidence in support of this model includes the results that interference with ER budding and biogenesis of vesicles involved in the ER to Golgi membrane depresses the formation of replication vacuoles (13,22,67). Furthermore, a large collection of IDTS target proteins are involved in both tethering and fusion of ER-derived vesicles to the Golgi compartment (68). There is evidence, however, that L. pneumophila may hijack ER-plasma membrane interactions or induce novel pathways to direct peripheral ER to interface directly with the plasma membrane during the early stages of vacuole formation.…”
Section: Discussionmentioning
confidence: 90%
“…Evidence in support of this model includes the results that interference with ER budding and biogenesis of vesicles involved in the ER to Golgi membrane depresses the formation of replication vacuoles (13,22,67). Furthermore, a large collection of IDTS target proteins are involved in both tethering and fusion of ER-derived vesicles to the Golgi compartment (68). There is evidence, however, that L. pneumophila may hijack ER-plasma membrane interactions or induce novel pathways to direct peripheral ER to interface directly with the plasma membrane during the early stages of vacuole formation.…”
Section: Discussionmentioning
confidence: 90%
“…L. pneumophila secretes ϳ300 effector proteins into the host cytosol via a T4SS that it uses to manipulate the process of vacuole maturation (8,25). The identification of effector proteins that have important intracellular functions has been challenging because elimination of a single effector, or even large clusters of effectors, does not typically interfere with the ability of L. pneumophila to replicate intracellularly (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have increased the number of identified T4SS effectors to more than 300 (22)(23)(24)(25)(26)(27)(28). We created a plasmid library containing the majority of effector proteins expressed from a constitutive low-expression vector.…”
mentioning
confidence: 99%
“…Its ability to replicate inside macrophages requires the Icm/Dot type IV secretion system (T4SS), which translocates approximately 300 effector proteins into host cells. 103 A screen for regulators of icmR expression, which encodes a chaperone component of the T4SS, identified CpxR as a positive regulator. 104 CpxR bound to the icmR control region in vitro, which contains a conserved CpxRbinding sequence, and a cpxR null mutation reduced expression of an icmR-lacZ translational fusion.…”
Section: Regulation Of Pili By the Cpx Responsementioning
confidence: 99%